Design of Point to Point Access Using Dense Wavelength Divison Multiplexing - Jhonatan Andreas Sinaga (Brilliance: Research of Artificial Intelligence, 2022)
In this research, a point to point access is designed on an optical communication network to see the performance parameters of bit error rate and q-factor. The research was conducted using OptiSystem software version 17, with design specifications such as a wavelength of 1555 nm, a range of 100 km, a number of 40 channels, and a frequency of 100 GHz. In this study, the best BER (Bit Error Rate) value was 10-6. Meanwhile, the Q-factor value is 4.8, which means that the Q-factor value has met the standard if it is seen from the BER value obtained. There are several factors that have a major influence on the design of fiber optic networks, such as power, amplifier specifications and bandwidth values. To minimize the enlargement of the BER (Bit Error Rate) and Q-factor values ??that come out.